Economics today - Miller, Roger Leroy (San Francisco, 1974)
In order to allow professors more flexibility in their use of the innovative content of Roger Miller's Economics Today, the material is now available in separate micro and macro versions. The Macro View includes all th macro chapters of the criginal hardcover text, plus brief micro material to give the volume continuity and make it self-contained. There are updated Issues dealing with wage and price controls, the international monetary crisis, and oil import quotas. In add on, tables and charts have been made currit with 1972 data.
Keywords: Macroeconomics